Numerical modeling of three dimensional time-dependent gas flow through porous objects with energy-releasing sources - Lutsenko, Nikolay Anatolievich (Computational Continuum Mechanics, 2016)
The gas flow in the gravity field through porous objects with energy sources is investigated when the self-regulation of flow rate of the gas passing through the porous object takes place. In other words, in the investigated porous objects the gas pressure on the object borders is known, but the flow rate of the gas passing through the object is unknown a priori and has to be found from the solution of the problem. Such processes are typical for the heat sources in porous media, which result from natural or man-made disasters (like the exploded unit of the Chernobyl NPP). In the present work the mathematical model and the original numerical method, based on a combination of explicit and implicit finite difference schemes, have been developed for studying the time-dependent processes in the three-dimensional porous self-heating objects. The advantage of the numerical model is its ability to describe unsteady processes under both natural convection and forced filtration. Using computational experiment, the air cooling of porous three-dimensional objects with different heat distribution at a constant total energy release is studied. It is shown that among other factors the distribution of energy-releasing sources with fixed intensity in horizontal sections has an influence on the total heating of the object.